2002
DOI: 10.1038/nature00847
|View full text |Cite
|
Sign up to set email alerts
|

Sequence and analysis of chromosome 2 of Dictyostelium discoideum

Abstract: The genome of the lower eukaryote Dictyostelium discoideum comprises six chromosomes. Here we report the sequence of the largest, chromosome 2, which at 8 megabases (Mb) represents about 25% of the genome. Despite an A + T content of nearly 80%, the chromosome codes for 2,799 predicted protein coding genes and 73 transfer RNA genes. This gene density, about 1 gene per 2.6 kilobases (kb), is surpassed only by Saccharomyces cerevisiae (one per 2 kb) and is similar to that of Schizosaccharomyces pombe (one per 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
103
0
10

Year Published

2003
2003
2007
2007

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 166 publications
(115 citation statements)
references
References 31 publications
2
103
0
10
Order By: Relevance
“…It is not clear if all of the sequences missing from the draft human genome sequence are represented in the bacterial libraries. The recent sequencing of two microbe genomes (Plasmodium falciparum and Dictyostelium discoideum) has shown that a high chromosomal AT content prevents the construction of large-insert BAC libraries (Gardner et al, 2002;Glockner et al, 2002). Only because large genomic fragments of these microbes are clonable in YACs did the authors succeed in constructing scaffolds of contiguous DNA sequence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not clear if all of the sequences missing from the draft human genome sequence are represented in the bacterial libraries. The recent sequencing of two microbe genomes (Plasmodium falciparum and Dictyostelium discoideum) has shown that a high chromosomal AT content prevents the construction of large-insert BAC libraries (Gardner et al, 2002;Glockner et al, 2002). Only because large genomic fragments of these microbes are clonable in YACs did the authors succeed in constructing scaffolds of contiguous DNA sequence.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we suggest an approach that may help both with the assessment of the magnitude of the problem, and with its resolution. It has been reported that ATrich genomic fragments and long inverted-repeats are more stable in yeast than in E. coli (Hayashi et al, 1993;Gardner et al, 2002;Glockner et al, 2002). Transformation-associated recombination (TAR) cloning is a recently developed yeast-based method for the selective cloning of a specific chromosomal region from a complex genome.…”
Section: Introductionmentioning
confidence: 99%
“…A seqüência do cromossomo 2, o maior deles, foi recentemente publicada e corresponde a ~25% do genoma com 2.799 genes preditos. Análises destas seqüências mostraram uma densidade gênica menor em D. discoideum (1 gene/2,6kb) que a observada na levedura S. cerevisiae (1 gene/2kb) (Glockner et al, 2002). O tamanho do genoma de D. discoideum fortalece a visão do seu posicionamento filogenético próximo à base da evolução dos metazoários, anterior à separação dos fungos e metazoários, porém posterior à divergência do reino das plantas (Baldauf et al, 2000;Glockner et al, 2002).…”
Section: Fosforilação Reversível De Proteínas Em Dictyostelium Discoiunclassified
“…Análises destas seqüências mostraram uma densidade gênica menor em D. discoideum (1 gene/2,6kb) que a observada na levedura S. cerevisiae (1 gene/2kb) (Glockner et al, 2002). O tamanho do genoma de D. discoideum fortalece a visão do seu posicionamento filogenético próximo à base da evolução dos metazoários, anterior à separação dos fungos e metazoários, porém posterior à divergência do reino das plantas (Baldauf et al, 2000;Glockner et al, 2002). Assim, por ser um eucarioto com um programa de desenvolvimento multicelular simplificado, pode ser útil no estudo da evolução dos metazoários (Aubry & Firtel, 1999 (Loomis et al, 1982;Devreotes, 1989;Kessin & Campagne, 1992;Gross, 1994;Kimmel & Parent, 2003 agregado assume a forma de um monte (agregado compacto) e as células do cume desta estrutura passam a exibir um padrão de expressão gênica distinto das demais.…”
Section: Fosforilação Reversível De Proteínas Em Dictyostelium Discoiunclassified
See 1 more Smart Citation